HIV/AIDS vulnerability among farm workers in the southern Freestate - Heideman, Estelle (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MPhil (Industrial Psychology. Africa Centre for HIV/AIDS Management))--University of Stellenbosch, 2010.